Analisis Kegagalan Material Waterwall Tube Boiler PLTU Ubon Banten 3 Lontar Unit 3 - Harun Al Rosyid; Jamal Firmansyah (Sekolah Tinggi Teknik - PLN, 2013)
In the combustion chamber of PLTU UBOH Banten 3 Lontar uses the waterwall tube (waterwall tube) for heating water to produce high pressure steam and turn a turbine, the heating of them used the principles of radiation and koveksi. Therefore, a problem often encountered is thinning and leaking waterwall tube. Depletion problem waterwall tube is a very urgent issue to be addressed immediately. In this study, the writer focused on the observation and analysis of material failure in the main area of ​​the tube wall material. The writer intends to conduct testing of waterwall tube material with Metallography testing process. The objective of test is to determine the layer thickness and the chemical elements that there is in the material and visual observations of the surface after cleaning which is to determine the level of damage that occurs in the depletion that is caused by shotblasting.